The learning styles of optometry students at the University of the Free State - Kempen, E. (University of the Free State, 2015)
In the research project reported here, a study was conducted with a view to providing direction to educators in the Department of Optometry at the University of the Free State (UFS), in order for them to create a learning environment that would motivate students to achieve excellence in the competencies and knowledge required to qualify as competent Optometrists. This study was initiated in response to the identification of a gap in the knowledge regarding the way undergraduate Optometry students at the UFS in 2014 perceived and processed knowledge, known as their learning styles. Higher education in South Africa faces many challenges. The improvement of graduate production for economic, social, and cultural development highlights the need to revitalise the current educational strategies to minimise the wastage of talent and to prevent the failure of academic careers. According to both scholarly and popular literature, the use of learning styles as an educational strategy will become more important as it is seen as one of the success factors in higher education, contributing to the effectiveness of learning. The aim of the study was to describe the learning styles of Optometry students at the UFS with a view to creating a better understanding of how students acquire learning and to enhance the learning environment accordingly. This was attained by the means of the following objectives, namely obtaining data to create a deeper understanding of the significance of learning styles in the curriculum framework of higher education institutions and identifying and describing the learning styles of the Optometry students at the UFS according to Kolb’s Learning Style Inventory (LSI). In the study use was made of a quantitative design. Data were gathered by means of a questionnaire survey (Kolb’s LSI) among the registered undergraduate Optometry students at the UFS in 2014. From the findings of the questionnaire survey, the conclusion was drawn that the undergraduate Optometry students of 2014 employed the four learning styles according to the following order of priority: (i) Converger; (ii) Assimilator; (iii) Accommodator; and (iv) Diverger. The findings also indicated that neither of the variables of age, gender, academic year, or ethnicity had any effect on the students’ preference of learning style. These findings, as well as the data collected from the literature survey, were incorporated in the formulation of recommendations for the enhancement of the four components of Kolb’s learning cycle, as indicated in the aim of the study. Attention was given to the enhancement of the learning environment most suitable for the two most preferred learning styles. Depending on the learning outcomes and based on the knowledge of the preferred learning styles, the lecturer may choose to match or mismatch the learning styles of the students to the teaching method, or to apply a multi-style teaching approach. With the learning styles of the undergraduate students identified, the Department of Optometry, through implementation of the recommendations, may create an optimal teaching and learning environment that will accommodate the diversity of this generation of undergraduate students in terms of different learning styles.

In die navorsingsprojek waaroor hier verslag gedoen word, is ŉ studie uitgevoer met die doel om leiding aan onderriggewers in die Departement van Optometrie aan die Universiteit van die Vrystaat (UV) te verskaf, sodat hulle ŉ leeromgewing kan skep wat studente motiveer om uitnemendheid te ontwikkel in die vaardighede en kennis benodig om as bevoegde oogkundiges te kwalifiseer. Die studie is geïnisieer in respons op ’n leemte wat geïdentifiseer is rakende die wyse waarop die 2014- voorgraadse Optometriestudente aan die UV kennis bekom en verwerk, bekend as studente se leerstyle. Hoër onderwys in Suid-Afrika staar baie uitdagings in die gesig. Die dringendheid om die uitset van gegradueerdes te verbeter met die oog op ekonomiese, sosiale en kulturele ontwikkeling, beklemtoon die behoefte wat bestaan om die huidige opvoedkundige benaderings te vernuwe om die verkwisting van talent te verminder en die mislukking van akademiese loopbane te voorkom. Volgens beide vakgerigte en populêre literatuur sal die gebruik van leerstyle as 'n opvoedkundige strategie al belangriker word, aangesien dit beskou word as een van die suksesfaktore in hoër onderwys en dit bydra tot die effektiwiteit daarvan. Die doel van die studie was om die leerstyle van die 2014-Optometriestudente aan die UV te beskryf met die oog daarop om 'n beter begrip te kry van hoe studente leer en die leeromgewing dienooreenkomstig te verbeter. Dit is bereik deur middel van die volgende doelwitte, naamlik die verkryging van data om 'n beter begrip van die betekenis van leerstyle in die kurrikulumraamwerk van hoëronderwysinstellings te bewerkstellig, en die identifisering en beskrywing van die leerstyle van die Optometriestudente aan die UV aan die hand van Kolb se Leerstylinventaris (LSI). In die studie is gebruik gemaak van 'n kwantitatiewe navorsingsontwerp. Data is ingesamel deur middel van 'n vraelysopname (Kolb’s LSI) wat in 2014 deur die geregistreerde voorgraadse Optometriestudente aan die UV voltooi is. Uit die resultate van die vraelysopname blyk dit dat die voorgraadse Optometriestudente wat gedurende 2014 aan die ondersoek deelgeneem het, die volgende vier leerstyle, in prioriteitsvolgorde, geïdentifiseer het: (i) Konvergeerder; (ii) Assimilator; (iii) Akkommodeerder; en (iv) Divergeerder. Die bevindinge het ook aangedui dat nie een van die veranderlikes van ouderdom, geslag, akademiese jaar en etnisiteit enige effek op die studente se voorkeurleerstyl gehad het nie. Hierdie bevindinge, asook die data uit die literatuuropname, is geïnkorporeer in die formulering van aanbevelings vir die verbetering van die vier komponente van Kolb se leersiklus, soos aangedui in die doel van die studie. Aandag is gegee aan die verbetering van die leeromgewing vir die twee prioriteitsleerstyle. Afhangende van die leeruitkomste en gebaseer op die kennis van die voorkeurleerstyle, kan die dosent kies om die onderrigmetode by die leerstyl van die studente aan te pas, of om dit juis te laat verskil, of om 'n multistyl-onderrigbenadering te gebruik. Met die leerstyle van die voorgraadse studente geïdentifiseer, kan die Departement van Optometrie, deur die implementering van die aanbevelings, 'n optimale onderrigen leeromgewing skep wat die diversiteit van hierdie generasie van voorgraadse studente ten opsigte van verskillende leerstyle, kan akkommodeer.
Dissertation (M.HPE. (Health Professions Education))--University of the Free State, 2015.
Keywords: Learning styles; Educational strategy; Higher education; Quantitative research; Learning environment; Curriculum enhancement; Kolb’s learning style inventory; Optometry -- Study and teaching; Education, Higher -- Study and teaching; University of the Free State